The Relationship Between Dietary Inflammatory Index and All-Cause, Cardiovascular Disease-Related, and Cancer-Related Mortality - Gao Y; Wang Y; Zhang D; Wu T; Li Q (Journal of Multidisciplinary Healthcare, 2023)
Yonghong Gao,1 Yan Wang,1 Dandan Zhang,2 Tingting Wu,1 Qingwei Li1 1Department of Cardiology, Shanghai Jinshan District Tinglin Hospital, Shanghai, 201505, People’s Republic of China; 2Department of General Practice, Shanghai Jinshan District Tinglin Hospital, Shanghai, 201505, People’s Republic of ChinaCorrespondence: Qingwei Li, Department of Cardiology, Shanghai Jinshan District Tinglin Hospital, Shanghai, 201505, People’s Republic of China, Email tel18930810663@163.comBackground: In the general population of the United States (U.S.), the relationship between dietary inflammatory index (DII) and mortality (all-cause, cardiovascular disease (CVD)-related, and cancer-related) is still unclear. Therefore, in this research, we examined the association of DII with mortality caused by all-cause, CVD-related, and cancer-related causes.Methods: Data from the National Health and Nutrition Examination Survey (NHANES) from 1999– 2018 was used for exploring the link between DII and all-cause, CVD-related, and cancer-related mortality through the use of Cox proportional hazard models and restricted cubic spline model. In addition, subgroup analyses were further performed.Results: The study included 29,013 individuals from the NHANES from 1999 to 2018. The DII scores were nominated as low (T1: − 5.281– 0.724), medium (T2: 0.725– 2.513), and high-grade inflammation (T3: 2.514– 5.795), with T1 serving as the reference group. The linear positive correlation between DII and all-cause and CVD-related mortality was studied using Cox regression analysis. In the full-adjusted model, as compared with the individuals with T1 DII scores, adjusted odds ratios with 95% confidence intervals for all-cause and CVD-related mortality were 1.149 (1.059, 1.247), and 1.186 (1.084, 1.297), as well as 1.197 (1.032, 1.387), and 1.198 (1.019, 1.409), respectively. However, there was no statistical significance between DII and cancer-related mortality. The RCS plot also showed a significant increase in all-cause and CVD-related mortality with increased DII. Nevertheless, as DII scores increased, cancer-related mortality first increased and then decreased.Conclusion: All-cause and CVD-related mortality are linked independently to high DII scores, independently. Further study of the association of DII scores with mortality caused by all-cause, CVD-related, and cancer-related causes is necessary to explore.Keywords: all-cause mortality, cancer-related mortality, cardiovascular disease-related mortality, dietary inflammation index, National Health and Nutrition Examination Survey